Subsidi Silang Pendidikan: Solusi Ekonomi untuk Mengurangi Kesenjangan Sekolah Kota dan Desa - Muh. Hasbi (Al-Buhuts, 2024)
Educational inequality between urban and rural areas remains a major issue in the development of education in Indonesia. Differences in the quality of school infrastructure, access to technology, teacher competencies, and the economic capacity of communities have resulted in significant disparities in educational quality. Schools in urban areas generally possess more comprehensive educational facilities compared to those in rural regions. This condition has contributed to limited educational access for rural communities and high school dropout rates caused by economic constraints. This study aims to analyze educational cross-subsidization as an economic solution to reduce educational disparities between urban and rural schools in Indonesia. This study employs a library research method with a descriptive qualitative approach. Data were obtained from national and international scientific journals published between 2003 and 2024. The findings reveal that educational cross-subsidization represents a mechanism for redistributing educational resources from communities or regions with higher economic capacity to underprivileged communities. Cross-subsidy policies can be implemented through school operational assistance, educational scholarships, the development of rural school infrastructure, educational technology support, and the equitable distribution of qualified teachers. Educational cross-subsidization has proven effective in improving access to education, enhancing the quality of rural school facilities, reducing school dropout rates, and expanding learning opportunities for economically disadvantaged communities. However, the implementation of educational cross-subsidization still faces several challenges, including infrastructure disparities, limited budget supervision, digital inequality, and the low managerial capacity of local educational institutions. Therefore, inclusive, transparent, and sustainable educational policies are required to ensure that educational cross-subsidization can promote equitable national educational quality and support the balanced development of Indonesia’s human resources